2009
DOI: 10.1177/104063870902100210
|View full text |Cite
|
Sign up to set email alerts
|

Using Roquefortine C as a Biomarker for Penitrem A Intoxication

Abstract: Abstract. Penitrem A is a well-recognized tremorgenic mycotoxin produced by several Penicillium spp. However, most natural cases of penitrem A intoxication have been associated with Penicillium crustosum. Another Penicillium sp., Penicillium roqueforti, is used for the production of blue cheese and is found in silage and feeds. Penicillium roqueforti produces a mycotoxin, roquefortine C, which is also produced by P. crustosum. In contrast to a tremorgenic syndrome produced by penitrem A, roquefortine C toxicos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In vivo , reversible paralytic effects were reported in cows that ingested P. roqueforti -contaminated feed grains containing an average roquefortine C concentration of 25.3 mg/kg [ 197 ]. Tiwary et al [ 272 ] reported roquefortine C did not appear to be responsible for tremorgenic effects and could be quantified as biomarker for penitrem A exposure. Tüller et al [ 95 ] feeding sheep 0, 10 and 50 mg/sheep/day of roquefortine C did not report any effects on chemical and hematological parameters.…”
Section: Effect Of Mycotoxins Ingestion On Ruminants: Inmentioning
confidence: 99%
“…In vivo , reversible paralytic effects were reported in cows that ingested P. roqueforti -contaminated feed grains containing an average roquefortine C concentration of 25.3 mg/kg [ 197 ]. Tiwary et al [ 272 ] reported roquefortine C did not appear to be responsible for tremorgenic effects and could be quantified as biomarker for penitrem A exposure. Tüller et al [ 95 ] feeding sheep 0, 10 and 50 mg/sheep/day of roquefortine C did not report any effects on chemical and hematological parameters.…”
Section: Effect Of Mycotoxins Ingestion On Ruminants: Inmentioning
confidence: 99%
“…Feed analysis performed was not able to find PA in detectable concentrations. In literature, it has been reported that PA is more difficult to isolate than RC, but RC is always associated with PA in tremorgenic toxicosis caused by PA (Tiwary et al, 2009). Thus, RC is considered a valuable diagnostic marker for PA intoxication (Tiwary et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In literature, it has been reported that PA is more difficult to isolate than RC, but RC is always associated with PA in tremorgenic toxicosis caused by PA (Tiwary et al, 2009). Thus, RC is considered a valuable diagnostic marker for PA intoxication (Tiwary et al, 2009). Also, results for other potentially involved pathogens were negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytic methods include identification of the mould through culture of the organism or detection of the toxins themselves (Eriksen et al 2010;Rundberget et al, 2002;Young et al, 2003). Liquid chromatography has also been used to screen for the specific toxins penitrem A and roquefortine in serum (Puschner, 2009) and urine samples (Tiwary, 2009). These tests are available from some specialised diagnostic laboratories.…”
Section: Resultsmentioning
confidence: 99%